Synthesis and crystal structure of 5,10-bis(phenylsulfonyl)tetrahydrodibenzopentalene - Toshiki Sakami; Hikaru Watanabe; Takuma Sato; Yasuhiro Okuda; Kan Wakamatsu; Haruo Akashi; Akihiro Orita (Acta Crystallographica Section E: Crystallographic Communications)
5,10-Bis(phenylsulfonyl)tetrahydrodibenzopentalene, C28H22O4S2, 1, was successfully synthesized via the photocatalyst-promoted hydrogenative transannulation of disulfonylcyclooctatetraene, 2, using perylene as the photocatalyst in the presence of (i-Pr)2NEt under UV-light irradiation (398 nm, 30 W). In this reaction, the cyclooctatetraene moiety of 2 underwent hydrogenative transannulation, yielding 1. Single-crystal X-ray analysis revealed that both enantiomers of 1 are arranged alternately along the a axis of the unit cell. The structure features a wide V-shaped motif consisting of 6–5–5–6 fused rings, with a dihedral angle of approximately 97.2° between the planes of the terminal phenylene rings. Additionally, a pair of phenylsulfonyl groups were observed at the exo positions relative to the V-shaped array.